Analisis Daya Saing Ekspor Teh Indonesia di Pasar Asia Tenggara Tahun 2012-2021 - Sapto Sapto; Sri Marwanti; Dewi Hastuti; Hilmi Arija Fachriyani (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2024)
Tea is one type of beverage that has many fans. In addition to having a distinctive taste, tea is also beneficial for the body. The high demand makes tea one of the export commodities in various countries, especially Indonesia. The area of tea plantations in Indonesia makes Indonesia the second largest country as a tea exporter in Southeast Asia after Vietnam. The study aimed to determine the competitiveness and trend of Indonesian tea export competitiveness in the Southeast Asian market. The basic method uses descriptive analysis methods. Data uses secondary time series data obtained from various official sources such as ITC Trade Map, Food and Agriculture Statistics (FAOSTAT), and other sources of information obtained from books, articles, and journals. The analysis method uses Revealed Comparative Advantage (RCA) to determine the competitiveness of Indonesian tea commodity exports and the Export Competitiveness Index (ECI) method to determine the trend of Indonesian tea competitiveness. The study results showed an average RCA value> 1, which is 2.29, which means that Indonesian tea has strong competitiveness in the Southeast Asian market.